2016
DOI: 10.1007/s00158-016-1611-2
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization under thermo-elastic buckling

Abstract: The focus of this paper is on topology optimization of continuum structures subject to thermally induced buckling. Popular strategies for solving such problems include Solid Isotropic Material with Penalization (SIMP) and Rational Approximation of Material Properties (RAMP). Both methods rely on material parameterization, and can sometimes exhibit pseudo buckling modes in regions with low pseudo-densities.Here we consider a level-set approach that relies on the concept of topological sensitivity. Topological s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The designed layout optimized for u p = 0.05 shows that the horizontal compression is dominant with the additional small bending due to the vertical force. These optimum layouts also agree well with the layouts obtained via linear compliance minimization in which a cantilever with only central axial load is considered [15]. Adding a temperature does not change the optimum layout of u p = 0.05, although the required mechanical load Fig.…”
Section: Short Cantilever Beamsupporting
confidence: 80%
See 3 more Smart Citations
“…The designed layout optimized for u p = 0.05 shows that the horizontal compression is dominant with the additional small bending due to the vertical force. These optimum layouts also agree well with the layouts obtained via linear compliance minimization in which a cantilever with only central axial load is considered [15]. Adding a temperature does not change the optimum layout of u p = 0.05, although the required mechanical load Fig.…”
Section: Short Cantilever Beamsupporting
confidence: 80%
“…According to these results, it can be therefore concluded that the proposed optimization method produces the slit and struts, which are beneficial in maximizing buckling capacity for the given material volume. The study also helps to understand why slits and struts are found in optimum structures when mechanical buckling load is considered through a linear buckling constraint [59], or randomly imposed geometric imperfections [41]. When the present scheme is incorporated within the multiscale optimization [53], hierarchical lattice-like structures are expected as optima in the small-scale regime [60].…”
Section: Mechanical Loading Onlymentioning
confidence: 91%
See 2 more Smart Citations
“…This can be achieved either by tracing the phase borders or by introducing a density field that describes the material configuration in each point of the design space. The phase borders are subject to optimization in level‐set approaches, which became popular recently due to the inclusion of coupled mechanical problems, eg, buckling and thermal induced stresses, and stress and manufacturing constraints . In density field‐based approaches, a discrete density or a continuous density interpolation is introduced.…”
Section: Introductionmentioning
confidence: 99%